(3QSGdI JbdjO SajQ GdbOQIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdMeO dehdGfG hMOg dGTQjc dg ai GdSQGA hGdVQGA hGdTOI hGdQNGA ef YHO ehdGfG heedhcg bGFe GdReGf Edi GdTjN SajQ GdbOQI aNQ GdehMOjf hcdeJge GdYdjG CHj YHO Gddg eMeO Hf hgH GdbQTi s
(3BNQgG (B:s
(3hJhUd LhGHGJgG hJfaP Edi hdOi Ydi hMSjf GdeCPhfjf ai GdOYhI CjOgeG Gdehdi HhUhdgeG Edi GdLGQjI Je GdJbdjO hGdMeO dehdGfG hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B22s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3abg GdePGgH GdCNQis